Ode to UMPSA: A Tribute on Labor Day - Noraisah Nurul Fatwa, Mohd Razali (UMPSA, 2025)
On this dawn of May's proud light, We lift our hearts, our pens, our sight, To UMPSA's halls where dreams ignite, And labour glows in noble might